Urgensi Harmonisasi Kepailitan Lintas Batas Terhadap Kewenangan Kurator dalam Eksekusi Aset Debitor (Studi Implementasi Uncitral Model Law di Korea Selatan - Zahra, Fatimah Az; Meliala, Aurora Jillena (Jurnal Locus Penelitian dan Pengabdian, 2025)
The development of global trade has led to the emergence of cross-border insolvency, where the debtor’s assets are scattered in several countries and create legal challenges for curators in executing bankruptcy estates. Indonesia, which still adheres to the territoriality principle under Law Number 37 of 2004, faces significant barriers in recognizing and enforcing foreign bankruptcy decisions, resulting in ineffective cross-jurisdictional asset resolution and losses for creditors. This research employs a normative juridical method and a comparative approach by examining the implementation of the UNCITRAL Model Law on Cross-Border Insolvency in South Korea. The findings show that legal harmonization through the adoption of the Model Law can strengthen the curator’s authority in executing assets across jurisdictions, as well as enhance legal certainty and creditor protection. It is recommended that Indonesia undertake bankruptcy law reform by adopting the principles of the UNCITRAL Model Law as an effort to modernize its national insolvency regime in response to global trade dynamics.